ÓZGE TILLI KLASSLARDA QARAQALPAQ TILIN OQÍTÍWDA OQÍWSHÍLARDÍŃ BILIM DÁREJELERIN ESAPQA ALÍW MÁSELELERI - Bekimbetova, G.R. (SCIENCE and SOCIETY, 2023)
This article discusses the issues of teaching the Karakalpak language in educational institutions where education is conducted in other languages, the development of students' language competencies.
Keywords: spoken karakalpak; scientific experience; foreign language classes; attitude; listening; speaking; reading